2014
DOI: 10.1017/s0007114514002918
|View full text |Cite
|
Sign up to set email alerts
|

High sodium intake during postnatal phases induces an increase in arterial blood pressure in adult rats

Abstract: Epigenetic studies suggest that diseases that develop in adulthood are related to certain conditions to which the individual is exposed during the initial stages of life. Experimental evidence has demonstrated that offspring born to mothers maintained on high-Na diets during pregnancy have higher mean arterial pressure (MAP) in adulthood. Although these studies have demonstrated the importance of prenatal phases to hypertension development, no evidence regarding the role of high Na intake during postnatal phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Therefore, the 12 weeks of HS diet may have little effect on mechanism regulating food intake in this model. It has been shown elsewhere that weaned rats drinking saline solution for water over 8 weeks 12 ate and grew less than respective controls. One may conclude that such approach may compromise overall animal nutrition and bring upon other hypertensive factors since previous studies have proposed that protein restriction can result in cardiovascular dysfunctions 12 .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Therefore, the 12 weeks of HS diet may have little effect on mechanism regulating food intake in this model. It has been shown elsewhere that weaned rats drinking saline solution for water over 8 weeks 12 ate and grew less than respective controls. One may conclude that such approach may compromise overall animal nutrition and bring upon other hypertensive factors since previous studies have proposed that protein restriction can result in cardiovascular dysfunctions 12 .…”
Section: Discussionmentioning
confidence: 88%
“…It has been shown elsewhere that weaned rats drinking saline solution for water over 8 weeks 12 ate and grew less than respective controls. One may conclude that such approach may compromise overall animal nutrition and bring upon other hypertensive factors since previous studies have proposed that protein restriction can result in cardiovascular dysfunctions 12 . Here, rats were exposed to sodium overload just after weaning, which is a crucial period of growth and maturation of several different physiological systems.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We found that high sodium intake in the first week of life was associated with adverse health outcomes in later life in several animal experiments [12,13,[32][33][34][35][36], whereas high sodium intake after this period was not, suggesting that the timing of taste exposure is important. In line with this, the results of Moreira et al [33] indicate that an overload of sodium intake during the postnatal period permanently alters the excretion patterns and spontaneous sodium intake patterns in adult- hood. Furthermore, sodium intake during postnatal period promotes salty food preferences in adulthood [33].…”
Section: Animal Studiesmentioning
confidence: 88%